Beyond PISA Rankings: A Comparative Analysis of Education Policy Transformation in Indonesia and China - Moh Shaefur Rokhman; Sitti Hartinah; Ihda Rosdiana (PT. Anagata Sembagi Education, 2026)
Education plays a crucial role in improving the quality of human resources and international competitiveness. Indonesia and China are two countries on the path to becoming developed nations with distinct educational systems, particularly in terms of governance and policy. This study aims to analyze the comparative transformation of Indonesia and China's education systems, emphasizing policy mechanisms, governance structures, and their implications for educational reform. This study employs a qualitative approach with a comparative study design through educational policy analysis. Data were obtained from national policy documents, international organization reports, and articles from reputable international and national journals. Data analysis was conducted using qualitative content analysis and cross-case comparative analysis. The results show that Indonesia's education system tends to be decentralized with implementation flexibility at the regional level, while China's system is more centralized with strong central government control and support from a data-driven evaluation system. These differences have implications for the effectiveness of policy implementation, the consistency of educational quality, and accountability mechanisms. This study contributes to the development of comparative education studies by offering a systems-based and policy-based analysis, as well as providing strategic recommendations for educational reform in Indonesia.